Electronic Communication as an Object of Linguistics - Nigar Naghiyeva (Indonesian Scientific Publication, 2026)
The article examines the linguistic features of electronic communication in the context of the rapid development of digital technologies and Internet discourse. The study analyzes the influence of computer-mediated communication on contemporary language processes at lexical, syntactic, stylistic, and graphic levels. Particular attention is paid to the transformation of traditional language norms in online interaction, including the widespread use of abbreviations, acronyms, emoticons, borrowings, and simplified syntactic structures. The paper also discusses the hybrid nature of Internet discourse, which combines characteristics of both written and spoken communication. In addition, the study considers the role of social media platforms and digital environments in the formation of new communicative practices and linguistic identities. The research demonstrates that electronic communication represents a dynamic and evolving sphere of modern language use shaped by the principles of interactivity, linguistic economy, and globalization. The increasing adaptation of English-based digital vocabulary and the emergence of new graphic and stylistic devices reflect ongoing changes in contemporary communication culture. The findings confirm that online discourse has become an important object of modern linguistic research and continues to influence the development of national languages in the digital era.